The austrian business cycle in the european context (2008)
The dating of business cycle turning points is still an important basis for economic policy decisions. The present study sets out to trace the Austrian business cycle for the Austrian economy for the period between 1976 und 2005, using quarterly national accounts data of Austria, Germany and the euro area. Three different filtering methods are applied: first-order differences, the Hodrick-Prescott filter and the Baxter-King filter. To all of them, two different methods of determining the business cycle are applied: the ad-hoc identification of the cyclical component and a dynamic factor model, taking into account the common cyclical variations for Austria, the euro area and the German economy. Subsequently, the Bry-Boschan algorithm serves to identify peaks and troughs of the cycle. Finally, the results are interpreted and compared with those of earlier studies on the euro area and the Austrian business cycle.